Rosmarinus officinalis and Methylphenidate Exposure Improves Cognition and Depression and Regulates Anxiety-Like Behavior in AlCl3-Induced Mouse Model of Alzheimer’s Disease - Malik, Nishat; Amber, Sanila; Zahid, Saadia (Frontiers in Pharmacology, 2022)
Alzheimer’s disease (AD) is a neurological illness causing sever cognitive impairment. AD patients also experience at least one of the neuropsychiatric symptoms including apathy, depression and anxiety during the course of their life. Acetylcholine esterase inhibitors are the available treatment options to alleviate cognitive deficits while Methylphenidate (MPH), a psycho-stimulant is considered for the treatment of apathy in AD patients. R. officinalis, a perennial herb, has been potentially known to have antioxidant and anti-inflammatory properties. The present study investigated the potential effects of MPH and R. officinalis in comparison to standard drug, Donepezil, on cognition, anxiety and depression in AlCl3-induced mouse model of AD. The animals were divided into eight groups (n=8, each). The results revealed that MPH and R. officinalis-treated groups significantly improved memory impairment while R. officinalis substantially reduced depression and anxiety as compared to other treatment groups. MPH treatment induced antidepressant effect and increased anxiety like behavior. Moreover, the AlCl3 exposure led to the formation of amyloid beta (Aβ) plaques in mice hippocampus but none of the tested drugs caused significant reduction in amyloid burden at the selected doses. The present study suggested the potential of R. officinalis to improve memory as well as neuropsychiatric symptoms in AD. Although, R. officinalis improved cognitive abilities however, did not reduce the amyloid plaque burden which indicates that memory enhancing effects of R. officinalis are due to some alternate mechanism that needs to be explored further.